Non-destructive Method for Asphalt Pavement Evaluation: A Review - Kamruzaman, Nurshazlynn; Mohd Kamaruddin, Dr. Nurul Hidayah (Recent Trends in Civil Engineering and Built Environment, 2021)
This paper presents a simple review of the non-destructive test (NDT) method in asphalt pavement evaluation. Three non-destructive testings including ground-penetrating radar (GPR), falling weight deflectometer (FWD), and ultrasonic pulse velocity (UPV) were reviewed. GPR test is to estimate asphaltic concrete density and thickness, FWD test is to check the modulus of resilient and UPV is to estimate the elastic properties. It can be found that small error and good correlation between NDT test and standard test. In the view of the literature review, it can be stated that the NDT test method is an interesting technology and able to contribute to the pavement application with acceptable measurement.